Noninvasive Ventilation in Palliative Care and Ethical Dilemma - Krivec, Uros; Caggiano, Serena (Frontiers in Pediatrics, 2020)
Significant difference exists between validated indications for noninvasive ventilation (NIV) use in children and current real life practice. Lately, dedicated centers have reported exponential growth of NIV use in children and adolescents. Upper airway obstruction, neuromuscular diseases, chronic lung/thoracic conditions and central respiratory drive failure remain the most prevalent indications. However, the need to alleviate respiratory failure related distress has been increasingly recognized in several other conditions. Palliative care in children with life limiting disorders is a complex continuum of activities. In order to provide the most appropriate care for the patients and their families, the management often oscillates between actively curative and purely supportive actions. Despite unprecedented therapeutic advancements, several neurologic, metabolic, hemato-oncologic, respiratory and other rare diseases remain with no curative options. Besides, attentiveness to relive suffering, awareness and availability have moved the boundaries of NIV use towards conditions formerly not considered suitable for such care. Still, NIV has limitations and can, if sustained in inappropriate circumstances, fail to provide relief. A structured professional frameshift should be available for support and ethical guidance in order to provide confidence to patients, families and all the involved caregivers.